British Thoracic Society community acquired pneumonia guideline and the NICE pneumonia guideline: how they fit together. Issue 1 (14th May 2015) - Lim, W S; Smith, D L; Wise, M P; Welham, S A
Abstract : The British Thoracic Society (BTS) guideline for the management of adults with community acquired pneumonia (CAP) published in 2009 was compared with the 2014 National Institute for Health and Care Excellence (NICE) Pneumonia Guideline. Of the 36 BTS recommendations that overlapped with NICE recommendations, no major differences were found in 31, including those covering key aspects of CAP management: timeliness of diagnosis and treatment, severity assessment and empirical antibiotic choice. Of the five BTS recommendations where major differences with NICE were identified, one related to antibiotic duration in low and moderate severity CAP, two to the timing of review of patients and two to legionella urinary antigen testing.